2021
DOI: 10.1016/j.jtocrr.2021.100224
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Safety Assessment of Lazertinib: Findings From Patients With EGFR Mutation-Positive Advanced NSCLC and Preclinical Studies

Abstract: Introduction Lazertinib is a potent, irreversible, brain-penetrant, mutant-selective, and wild-type–sparing third-generation EGFR tyrosine kinase inhibitor (TKI), creating a wide therapeutic index. Cardiovascular adverse events (AEs), including QT prolongation, decreased left ventricular ejection fraction (LVEF), and heart failure, have emerged as potential AEs with certain EGFR TKI therapies. Methods Cardiac safety of lazertinib was evaluated in TKI-tolerant adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…ILD was reported in two patients in each treatment group. Consistent with safety assessments in previous studies [ 17 , 18 , 30 ], which showed that lazertinib had no clinically relevant effects on QT interval, no severe QTc prolongation was observed in patients receiving lazertinib. Off-target inhibition of human epidermal growth factor receptor 2 (HER2) has been suggested as a possible underlying mechanism for EGFR TKI–associated cardiotoxicity.…”
Section: Discussionsupporting
confidence: 89%
“…ILD was reported in two patients in each treatment group. Consistent with safety assessments in previous studies [ 17 , 18 , 30 ], which showed that lazertinib had no clinically relevant effects on QT interval, no severe QTc prolongation was observed in patients receiving lazertinib. Off-target inhibition of human epidermal growth factor receptor 2 (HER2) has been suggested as a possible underlying mechanism for EGFR TKI–associated cardiotoxicity.…”
Section: Discussionsupporting
confidence: 89%
“…This study confirmed that lazertinib is effective in treating patients with non-small cell lung cancer and is more efficient in patients with T790M mutations. In a study exploring the cardiac safety of lazertinib, a total of 181 patients with EGFR mutation-positive advanced NSCLC treated with lazertinib were enrolled, and the result showed that lazertinib did not cause serious cardiotoxicity ( 16 ). The above findings suggest that lazertinib is effective in the treatment of NSCLC patients with the T790M mutation without serious toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this background, lazertinib has been found to exert minimal effects on cardiac function in both preclinical and clinical studies. 46 No patients experienced clinically significant QT prolongation or decreased left ventricular ejection fraction. Considering that lazertinib demonstrated comparable anti-tumor efficacy to osimertinib, it may be considered a relatively safer option in terms of cardiotoxicity.…”
Section: Osimertinib–a Friend or Foe?mentioning
confidence: 96%
“…Meanwhile, researchers have shown that lazertinib selectivity for HER2 over EGFR was 275-fold, compared to 6.7-fold for osimertinib, which implies that lazertinib has lower cardiotoxicity. 46 …”
Section: Osimertinib–a Friend or Foe?mentioning
confidence: 99%